Hierarchical effects on body size evolution and the macroecology of South American rainforest mammals - Jose A.F. Diniz-Filho; Rackel Balestra (Ecología Austral, 1998)
The relationship between geographic range size and body size analyzed at the continental scale for many species has been described recently by an envelope region defined in bivariate space and limited by ecological and physical constraints. These constraints can be explained by stochastic extinction related to m inimum population density and energetic theories for an optimal body size. However, since data are obtained for different species in a large taxonomic group, it is possible that these variables may be strongly affected by phylogenetic autocorrelation. In this paper, we analyzed data on geographic range size and body size for 87 species of Neotropical rainforest mammals from South America, searching for phylogenetic effects changing the shape of constraint space. We used a nested ANOVA design to evaluate and remove large scale hierarchical (phylogenetic) trends in the two variables. Body size was more affected by phylogenetic effects than geographic range size. After removing these effects, we noted that the two macroecological variables analyzed support the shape of constraint space previously observed in North American species. The most important aspect of our analyses is that a model for optimal body size related to life-history variations provides an useful theoretical framework to understand how processes of species dynamics can lead to the observed macroecological patterns.